Drivers and barriers of successful climate commitment development in the fast-food industry The case of MAX Burgers - Damdinova,Bairma (IIIEE Master Thesis, 2020)
Despite the fast food industry’s significant contribution to climate change, climate action plans are not common practice. Furthermore, there is a lack of academic works devoted to researching climate change issues within the fast-food industry. This thesis project examined the Swedish fast food chain MAX Burgers’ involvement with climate responsibility. By applying an internal and external influences framework, this thesis analysed drivers and barriers regarding the development of MAX’s climate commitment work. The thesis drew on empirical data from “grey literature” and seven in-depth interviews with MAX Burgers’ former and current top management representatives and the company’s external consultants on carbon footprint assessment and carbon compensating schemes. The findings suggested that MAX Burgers encountered eight key tipping point-events in its development that influenced and shaped its leadership position that pushes for carbon-reduction in the fast-food industry. Based on the narrative of MAX Burgers’ climate responsibility development, the analysed drivers emerging from within the organisation, particularly top management and ethical motives, proved to be the strongest push toward the carbon-reducing initiatives. The external influences, such as the regulatory influence, served as both driving and challenging forces. The lack of clarity in Swedish tax regulations related to carbon offsetting costs challenged MAX Burgers and resulted in a four-year court case. However, driven by the poor governance in combination with the ethical motives “to be a role model” in the market, the fast-food chain contributed to the industry by enabling incentives for spending on voluntary carbon offsetting projects. Other external influences emerging from suppliers, the public, and technological advancements were found to challenge MAX’s climate commitment development. Public concerns and criticism raised by Swedish researchers and other stakeholders have steadily been overcome, responded to, and endured by the fast-food chain. The company’s transparency and consistent communications on their climate responsibility work gain the trust of their customers and the Swedish nation overall. For other fast-food chains in Sweden, it might be easier to implement the same carbon neutral and positive approach because MAX has already paid its share to change the tax regulations and pushed the market to comply with climate action plan requirements. For policymakers, research implies that there should be a separation between leaders and followers. Therefore, policymakers could create incentives based on the scale of efforts in a climate action plan.
Keywords: fast-food industry; business sustainability; climate action plan; climate responsibility